Ciclo biológico y aspectos del comportamiento de Oligonychus sp. (Acarina: Tetranychidae) en Persea americana Mill., en laboratorio. - Ramírez López, Sharon Marion (2015)
Infested leaves were collected in cultivated fields of the new areas of irrigation Chavimochic, Sector IV, with the purpose of determining the biological cycle of Oligonychus sp. And aspects of its behavior in Persea americana. The samples were transferred to the Laboratory of Quality Control of the Board of Users of Pressurized Irrigation of the District of Irrigation of Moche, Virú and Chao. The experimental design consisted of 25 repetitions taken at random, with an only individual of Oligonychus sp. per experimental unit. The research was conducted during the period September 2014 – February 2015. In order to determine the gender Oligonychus sp., samples were sent to the National Service of Agrarian Health where this was confirmed. 3 fertilized females were isolated per experimental unit for the biological cycle of Oligonychus sp. and they were placed in foliar disks of 19 mm in diameter of leaves of avocado var. Hass. One egg was isolated per disk, completing 25repetitions.The biological cycle was: egg 7.64±1.05 days; larva 1.64±0.62 days; protonymph 3.52±0.70 days; deutonymph 4.40±0.57 days and longevity for adult female of 10.47±0.87 days and adult male 5.75±0.89 days. The entire biological cycle was 18.20 ± 1.76 days. To determine oviposition and preoviposition 20 couples were isolated and 1.5 min were determined for mating time, as well as the sex ratio of 1: 4.27 (Male:Female), the female oviposit 80.7 eggs on average during 10.9 days, as minimum 1 and maximum of 14 eggs. It was noted that damages caused by Oligonychus sp. appear more frequently in the adult state where the individual is more active during its fed.